Big Hole Drilling -- The State Of The Art - M. D. Lackey (Society for Mining, Metallurgy & Exploration, 1983)
The "Art" of Big Hole Drilling has been in a continual state of evolution at the Nevada Test Site since the start of underground testing in 1961. Emplacement holes for nuclear devices are still being drilled by the rotary drilling process, but almost all the hardware and systems have undergone many changes during the intervening years. The current design of bits, cutters, and other big hole drilling hardware results from contributions of manufacturers and Test Site personnel. The dual string, air lift, reverse circulation system was developed at the Test Site. Necessity was really the Mother of this invention, but this circulation system is worthy of consideration under almost any condition. Drill rigs for Big Hole drilling are usually adaptations of large Oil Well drill rigs with minor modifications required to handle the big bits and drilling assemblies. Steel remains the favorite shaft lining material, but a lot of thought is being given to concrete linings, especially precast concrete.